An overview of active compliance control for a robotic hand - Sadun, Amirul Syafiq; Jalani, Jamaludin; Abdul Sukor, Jumadi (Asian Research Publishing Network (ARPN), 2016)
It is vital to ensure that a robotic hand can successfully grasp the objects without damaging them. In order to allow a safe grasping, a technique called an active compliance control has been deployed. Active compliance control is an increasingly employed technique used in the robotic field such as service robotics, virtual reality and haptics, telemanipulation, human augmentation, and assistant. Recent research trends show that there are two main methods used in establishing active compliance control for robotic hand namely the force control and the impedance control. This paper highlights a summary of currently related works on active compliant control by using the force control and the impedance control. In addition, several control strategies of active compliance control are also discussed and highlighted for a safe grasping.